Narratives of identity and belonging: place and the everyday practices of immigrant Muslim women living in Fordsburg, Johannesburg - Bobat, Safiya (University of the Witwatersrand, Johannesburg, 2024)
This study set out to explore the ways in which identity and a sense of belonging are negotiated across place, space and time, taking into consideration the transnational and socio- political realities of the global world in which we live. It was located in Fordsburg, affectionately known as ‘Foodsburg’, an inner-city suburb of Johannesburg, South Africa that has a long, rich history of playing host to many different groups of people, particularly immigrant groups. This study asked the question: what are the experiences and understandings of Muslim, immigrant women living in Fordsburg on how their multiple identities and sense of belonging are negotiated across time and place in making sense of their lives through the everyday practices they engage in? Adopting a narrative methodological approach, multiple in-depth interviews, along with field notes and participant observations, were conducted with 10 participants who are all first-generation immigrant Muslim women from India, Bangladesh and the Philippines, currently living in Fordsburg. These narratives were analysed using a reflexive thematic analysis and a narrative constructionist analysis. Food and food practices were used as a lens to access narratives which opened up exploration into the complexity of negotiating identity and belonging within micro-spaces of home, broader spaces of community, and within transnational spaces. This study found that food is deeply symbolic, it is personal and social, it is local and global, and allows for deep insights into identity negotiations at multiple levels across time and place. Through the sensuous materiality that eating, preparing and purchasing food evoked, participants’ narratives revealed how identity is re-negotiated through the articulation of what is felt to be ‘known’ due to its familiarity and what is experienced as ‘new’ or ‘different’ and is integrated and accommodated. Through this articulation, the familiar and the new are 4 evaluated and assessed, losses and gains are negotiated, and new ways of being emerge. Themes of sensuous materiality, mobility, safety and transnational families emerged and highlighted the ways in which the concepts of memory, nostalgia, temporality, space and place are all intertwined in negotiating identity and belonging. This study provides valuable insights into the ways immigrant Muslim women negotiate their multiple identities and sense of belonging, through narratives of sensory engagement with the spaces they inhabit, local and transnational relationships, and broader socio-political discourses. It brought into conversation key concepts related to identity and belonging and related to place and space, deepening our understanding of these concepts by applying them to the immigrant experience, with a particular focus on gendered aspects of migration as related to women. Identity and place/space are both conceptualised as constructs that are continually evolving, and are reconstructed and reconceptualised across spatial and temporal lines. The ways in which identity and place/space articulate in these reconstructions and renegotiations is a key conceptual contribution of this study What is evident is that while immigrant women may actively work to carve out spaces of belonging and cultivate a sense of home in places in South Africa, like Fordsburg, the dominant prevailing xenophobic discourse within South African society impacts them on every level of their engagement.
A research report Submitted in fulfillment of the requirements for a Doctor of Philosophy, In the Faculty of Humanities , School of Human and Community Development, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; home; belonging; identity; food practices; migration; transnational relationships; xenophobia; SDG-11: Sustainable cities and communities